A modified adsorption material for efficiently removing malodorous gases, preparation method and application thereof
By modifying the multi-stage porous alumina metal halide, the problem of low efficiency and inactivation of adsorbents in wet environments is solved, and the adsorption effect of efficient hydrogen sulfide and ammonia is achieved, and the adsorption capacity and selection are improved. reduces costs.
Patent Information
- Application Number
- CN202411441258.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing adsorbents have low efficiency in removing hydrogen sulfide and ammonia in wet environments, and are prone to irreversible deactivation, resulting in small adsorption capacity and poor selectivity, making it difficult to achieve long-term stable and efficient removal.
The multi-stage porous alumina is modified by metal halides. Through gradient stirring and step-stage calcining technology, a modified adsorption material with wide mesoporous, narrow mesoporous and microporous structures is prepared to ensure uniform loading of metal halides. and sufficient reaction to improve adsorption performance.
Under the condition of relative humidity of 40%-90%, the penetration adsorption amount of ammonia and hydrogen sulfide of modified adsorbent materials reaches 40mg/g and 100mg/g respectively, which significantly improves adsorption efficiency and selectivity, reduces costs and Reduced waste emissions.
Smart Images

Figure CN118949917B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of adsorption materials, and in particular relates to a modified adsorption material for efficiently removing malodorous gases, a preparation method and an application thereof. Background Art
[0002] In recent years, with the rapid development of the national economy, the modernization level of industry and agriculture has been booming, and people's living standards have also been greatly improved. However, this has brought about serious environmental pollution problems, especially the presence of foul-smelling gases in people's production and living environment.
[0003] Hydrogen sulfide and ammonia are common malodorous gas pollutants in industrial production and daily life. In industrial production, the production of ammonia and hydrogen sulfide is mainly related to chemical reactions. For example, the industrial exhaust gas produced in the chemical production process contains a large amount of malodorous gases. Hydrogen sulfide and ammonia poisoning often occur in mining, coal chemical industry, petrochemical, papermaking and other production enterprises, especially when the equipment containing hydrogen sulfide is damaged or the pipelines and valves are leaking; in farms, ammonia and hydrogen sulfide are common harmful gases, and their excessive concentrations will have a negative impact on animal health and the breeding environment. Hydrogen sulfide has high solubility and volatility, and can quickly diffuse into the air of indoor living environments. When the concentration of hydrogen sulfide in indoor air exceeds a certain limit, it will cause a series of health problems, including eye and respiratory irritation, headache, dizziness, nausea, vomiting, chest tightness, drowsiness, coma and even death. Long-term exposure to high concentrations of hydrogen sulfide may also lead to chronic respiratory diseases, nervous system damage and liver damage. Hydrogen sulfide is also flammable and explosive. When its concentration reaches the explosion limit, it may cause an explosion accident when it encounters fire sources such as open flames or electric sparks, causing casualties and property losses. Ammonia has high volatility and solubility, and can quickly diffuse into the indoor air. After entering the human body, ammonia enters the blood through the alveoli and combines with hemoglobin to destroy the oxygen transport function. High concentrations of ammonia can irritate the eyes, nasal cavity and respiratory tract, causing symptoms such as burning eyes, coughing, and difficulty breathing. Inhalation in the short term mainly causes burning sensations in the eyes and skin. Irritation of the respiratory mucosa may cause coughing, chest tightness, pharyngitis, etc. Severe cases may cause pulmonary edema. Both hydrogen sulfide and ammonia have strong odors and toxicity, and are seriously harmful to the environment and human health.
[0004] At present, the main methods for removing hydrogen sulfide and ammonia include biological decomposition, plasma, photocatalytic conversion, adsorption, etc. The biological decomposition method has a low processing volume and high environmental requirements; the plasma method has a high purification efficiency but a high cost, and the high-energy ions and free radicals it produces will have an impact on the environment; the photocatalytic conversion method has high requirements for light sources and catalysts, and the reaction efficiency is low; compared with other purification methods, the adsorption method has a lower cost, the preparation and replacement of adsorbents are relatively simple, and does not require complex equipment and high operating costs. Some adsorbents can be regenerated by heating or cooling to restore adsorption performance, so that they can be recycled and reused to reduce resource waste.
[0005] Although traditional adsorbents (including activated carbon, silica gel, alumina, molecular sieves, natural clay, etc. that have not been artificially expanded) have a certain adsorption capacity for hydrogen sulfide and ammonia, they have problems such as small adsorption capacity, poor selectivity, and easy irreversible deactivation (difficult regeneration) under long-term use. Traditional adsorbents have limited removal efficiency for hydrogen sulfide and ammonia in humid environments and poor stability; generally speaking, higher humidity will reduce the adsorption capacity of the adsorbent and reduce the adsorption effect of hydrogen sulfide and ammonia; this is because increased humidity will cause water vapor on the surface of the adsorbent material to occupy the adsorption sites and compete with hydrogen sulfide and ammonia for adsorption. Alumina, as a porous material, has the advantages of large specific surface area, controllable pore structure, and good thermal stability. It is an ideal substrate for the preparation of high-efficiency adsorbents. However, pure alumina has limited adsorption capacity for hydrogen sulfide and ammonia. In order to improve its adsorption performance, active components are usually loaded on the surface of alumina to improve its gas selectivity. However, traditional microporous alumina is prone to pore blockage and reduced adsorption performance after loading modified substances and reacting with odorous gases NH3 and H2S in a humid environment.
[0006] Therefore, how to improve the topological structure of the carrier, optimize the selectivity of the modified substance and improve the reasonable occurrence of the carrier and the modified substance in a humid environment has become a serious problem that needs to be solved in the direction of the synergistic removal of malodorous gases NH3 and H2S. Therefore, it is of great significance to develop an adsorption material with good humidity adaptability and high efficiency in removing malodorous gases hydrogen sulfide and ammonia in a humid environment. Summary of the invention
[0007] In view of the above technical problems, the present invention discloses a modified adsorbent material, preparation method and application for efficiently removing malodorous gases. The modified adsorbent material provided by the present invention can efficiently remove malodorous gases such as hydrogen sulfide and ammonia in a high humidity environment, thereby improving environmental quality and protecting human health.
[0008] In order to achieve the above technical objectives, the present invention provides the following technical solutions:
[0009] A method for preparing a modified adsorbent material for efficiently removing malodorous gases comprises modifying hierarchical porous alumina with metal halides to obtain a modified adsorbent material for efficiently removing malodorous gases, wherein the malodorous gases include ammonia and / or hydrogen sulfide.
[0010] Furthermore, the pore structure of the multi-level porous alumina includes wide mesopores, narrow mesopores and micropores; the pore volume ratio of the wide mesopores, narrow mesopores and micropores is in the range of narrow mesopore volume: micropore volume = 10%-30%: 20%-40%: 20%-40%;
[0011] The specific surface area of the multi-level porous alumina is ≥250m 2 / g, and the average pore size of the multi-level porous alumina is ≥5nm. NH3 and H2S are both polar molecules, of which the diameter of NH3 molecule is about 0.37nm, and the diameter of H2S molecule is about 0.29nm. The reaction of the two molecules with the metal halide loaded on the surface of the material requires a "reaction site" with a large enough space. The large number of mesopores on the surface of the multi-level porous alumina used in the present invention can provide this "reaction site" well. The specific surface area of the multi-level porous alumina used in the present invention needs to reach 250m 2 / g or more, and the average pore size must be above 5nm to be suitable. The principle is: if the average pore size of multi-level porous alumina is less than 5nm, although the specific surface area is large, metal halides cannot enter or are blocked at the pores, and many pores have no load, so the actual effective specific surface area contributing to adsorption is small; if the average pore size is too large to make the specific surface area less than 250m 2 / g, even if the pores are loaded with metal halides, the total amount is still limited. Therefore, in the present invention, the specific surface area of the multi-level porous alumina used must reach 250m 2 / g or above and the average pore size reaches 5nm; suitable pores not only contribute to a higher specific surface area, but also allow metal halides to enter the pores for loading, without blocking the pores and allowing subsequent gases to be adsorbed to enter the pores for chemical adsorption, so that it can truly have a higher effective adsorption specific surface area.
[0012] Furthermore, the metal halide includes any one or more of copper chloride, nickel chloride, magnesium chloride, calcium chloride, and zinc chloride.
[0013] Furthermore, the metal halide is cupric chloride or a combination of cupric chloride and one or more of nickel chloride, magnesium chloride, calcium chloride and zinc chloride.
[0014] Furthermore, the method comprises the following steps:
[0015] (1) Dissolving metal halide in water to form a metal halide solution, adding multi-level porous alumina, and using a constant temperature shaker or an overhead mechanical stirrer to perform gradient graded stirring;
[0016] (2) placing the mixture treated in step (1) in a vacuum drying oven for drying;
[0017] (3) The material obtained by drying in step (2) is subjected to step-by-step calcination to prepare a modified adsorption material for efficiently removing ammonia and / or hydrogen sulfide.
[0018] Furthermore, in step (1), the shaking rate and temperature change of the constant temperature shaker meet the following conditions: shaking at 250-350 rpm at 50-60°C for 1-3 hours, then shaking at 150-250 rpm at 40-50°C for 1-3 hours, and finally shaking at 50-150 rpm at 30-40°C for 1-3 hours;
[0019] The rotation speed and temperature change of the overhead mechanical stirrer meet the following conditions: rotate at 300-500 r / min for 1-3 hours at 50-60°C, then rotate at 100-300 r / min for 1-3 hours at 40-50°C, and finally rotate at 20-100 r / min for 1-3 hours at 30-40°C;
[0020] In this step, the gradient grading speed and different temperature conditions are maintained in order to fully load the metal halide inside and on the surface of the carrier and improve the mass transfer efficiency. At 50-60°C with a high shaking / rotation speed of 250-350rpm (constant temperature shaker) or 300-500r / min (overhead mechanical stirrer), the convection movement inside the solution can be increased, and the metal halide solution can be better mixed, which is conducive to the uniform dispersion of the metal halide and its entry into the pores. At 50-60°C, the ion dispersion speed in the solution is accelerated so that the metal halide can quickly enter the microporous structure at the bottom of the multi-level porous alumina pores; after the loaded material has fully entered the microporous structure in the pores, the temperature is reduced to 40-50°C, and the shaking / rotation speed is reduced to 150-250rpm (constant temperature shaker) or 100-300r / min. n (overhead mechanical stirrer), lowering the rotation speed can not only reduce the possibility of damaging the pore structure, but also maintain the interaction force and collision frequency between molecules in the solution at a medium to high stirring speed, so as to promote more modified substances to be successfully adsorbed into the narrow mesoporous channels of hierarchical porous alumina; finally, the temperature is lowered to 40-50°C, and the shaking / rotation rate is reduced to 50-150rpm (constant temperature shaker) or 20-100r / min (overhead mechanical stirrer) for stirring for 1-3h because moderately reducing the stirring speed helps to reduce the interference caused by the diffusion movement of solid particles or molecules that have entered the pores. Under lower speed conditions, more materials can be effectively adsorbed and retained in the wide mesoporous positions in the channels.
[0021] In summary, the use of step-by-step speed stirring can make the loaded material fill the different pore structures in the multi-level porous alumina channels in a more uniform and thorough manner. And the simple process of step-by-step stirring avoids the long-term heating and stirring process. The stirring time is maintained at 1-3h per stage, and the stirring time needs to be strictly controlled. If the stirring time is too short, the metal halide cannot be fully loaded in the pores of the multi-level porous alumina, which reduces the pore utilization rate. However, if the stirring time is too long, the metal halide has already met the maximum amount that can be accommodated in the channel. Continuing to stir may cause too many impurities to adhere to the carrier surface. Therefore, the appropriate amount of stirring time helps the metal halide to fully contact with the carrier, promotes the metal halide to enter the pore structure, and gives the metal halide more opportunities to be adsorbed on the carrier surface and gradually diffuse and fill the pores.
[0022] The concentration of the metal halide in the metal halide solution in step (1) is 0.2-0.5 mol / L; by mass, the metal halide is 2-50 parts, and the multi-level porous alumina accounts for 100 parts; preferably, the metal halide is 10-35 parts, and more preferably 16.8 parts; the loading range is affected by the specific surface area and pore volume of the porous material. Too high a loading amount will cause pore blockage, and too low a loading amount will cause a large number of holes to be unable to be fully utilized, which will lead to unsatisfactory adsorption effects. It is necessary to ensure that the load material and the carrier maintain a certain ratio. Therefore, in the present invention, the concentration of the metal halide and the weight of the metal halide in the weight of the multi-level porous alumina need to be strictly controlled. The control of the above parameters not only ensures the ion loading inside and outside the porous alumina, but also ensures that the holes are not blocked.
[0023] Furthermore, in step (2), the drying method is vacuum drying, and the drying conditions are: drying temperature 100-180°C, drying time 0.5-16h. The drying conditions specified in this step can quickly dry excess water, so that the modified substance is better loaded on the carrier surface, and prevent impurities (such as impurities in the air during mixing and stirring) from adhering to the material surface, resulting in a decrease in adsorption effect.
[0024] Furthermore, in step (3), the conditions for the step-by-step calcination are: calcination under an inert gas atmosphere, first calcination at 350-450°C for 0.5-4h, then calcination at 250-350°C for 0.5-4h, and finally calcination at 150-250°C for 1-4h. In this step, the inert gas is used as a protective gas under an inert gas atmosphere and will not react with the metal halide and the carrier. First, calcination at a high temperature of 350-450°C helps to remove organic impurities and moisture in the modified material that has not been pre-calcined after loading, which is of great significance for improving the purity and selectivity of the modified material. The temperature is then reduced to 250-350°C. This process can avoid long-term excessively high temperatures causing changes in the alumina crystal form. Finally, the calcination temperature is reduced to 150-250°C to evenly disperse the metal halide on the carrier, ensuring that the active substance is stably fixed on the carrier surface, thereby promoting the combination of the metal halide active substance and the multi-level porous alumina, thereby improving the activity and stability of the modified material.
[0025] The invention improves the occurrence rationality and utilization rate of metal halides by controlling the specific surface area and average pore size of the multi-level porous alumina, so that the metal halides are fully dispersed on the alumina without agglomeration. The multi-level porous alumina used in the invention is obtained through purchase.
[0026] A modified adsorbent material for efficiently removing malodorous gases, wherein the concentration of ammonia or hydrogen sulfide in the mixed gas is 100ppb-6000ppm, and in a humid environment with a relative humidity of 5%-100%, the penetration adsorption amount of ammonia and hydrogen sulfide of the modified adsorbent material reaches 40mg / g and 100mg / g respectively;
[0027] The prepared modified adsorption material comprises a multi-level porous alumina carrier and an active substance loaded on the carrier; the active substance loaded on the carrier comprises M x Cl y ·nH2O、M x (OH) y Cl z , x ranges from 1 to 6, y ranges from 1 to 8, z ranges from 1 to 6, n ranges from 1 to 10, and M corresponds to copper, nickel, magnesium, calcium, and zinc metals.
[0028] Specifically, the active substance is loaded on the outer surface of the carrier and inside the pores of the carrier; when copper chloride is used for modification, the active substance contained in the obtained adsorption material includes CuCl2·2H2O, basic copper chloride Cu(OH)Cl; and also includes CuCl crystals;
[0029] An application of a modified adsorbent material, using the modified adsorbent material for the adsorption and removal of ammonia or hydrogen sulfide; and using the modified adsorbent material for the combined and simultaneous removal of ammonia and hydrogen sulfide from a mixed gas containing ammonia and hydrogen sulfide in a humid environment.
[0030] Beneficial effects brought by the technical solution of the present invention:
[0031] The modified adsorption material provided by the present invention uses metal halides as active components loaded on the surface of multi-level porous alumina, so that the modified multi-level porous alumina has high NH3 and H2S molecular recognition ability in a humid environment.
[0032] The modified adsorption material provided by the present invention improves the adsorption efficiency and selectivity by initiating an ion exchange reaction between the active substance loaded on the carrier and the target gas molecules, realizes the selective adsorption of specific gases such as ammonia and hydrogen sulfide, improves the processing efficiency, reduces the cost and reduces the waste emission.
[0033] The modified adsorption material provided by the present invention has good adsorption effect and stability for ammonia and hydrogen sulfide. Under the condition of relative humidity of 40%-90%, the penetration adsorption amount of ammonia and hydrogen sulfide of the modified adsorption material reaches 40 mg / g and 100 mg / g respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the pore size distribution curve of multi-level pore alumina.
[0035] Figure 2 This is the pore size distribution curve of multi-level porous alumina loaded with metal halide.
[0036] Figure 3 These are the XRD characterization diagrams of multi-level porous alumina, multi-level porous alumina loaded with 16.8% CuCl2 sample, and multi-level porous alumina loaded with 16.8% CuCl2 sample after H2S single component adsorption in 80% relative humidity atmosphere and dry atmosphere.
[0037] Figure 4 These are the XRD characterization diagrams of hierarchical porous alumina, hierarchical porous alumina loaded with 16.8% CuCl2 sample, and hierarchical porous alumina loaded with 16.8% CuCl2 sample after single-component NH3 adsorption in 80% relative humidity atmosphere and dry atmosphere.
[0038] Figure 5 This is the XRD characterization diagram of the multi-level porous alumina loaded with 16.8% CuCl2 sample after H2S and NH3 mixed adsorption in 80% relative humidity atmosphere and dry atmosphere.
[0039] Figure 6This is the XPS N1s spectrum of the multi-level porous alumina loaded with 16.8% CuCl2 sample after H2S and NH3 mixed adsorption in a dry atmosphere.
[0040] Figure 7 This is the XPS N1s spectrum of the multi-level porous alumina loaded with 16.8% CuCl2 sample after H2S and NH3 mixed adsorption in an atmosphere of 80% relative humidity (including wet environment).
[0041] Figure 8 This is the XPS S2p spectrum of the multi-level porous alumina loaded with 16.8% CuCl2 sample after H2S and NH3 mixed adsorption in a dry atmosphere.
[0042] Fig. 9 This is the XPS S2p spectrum of the sample after H2S and NH3 mixed adsorption on the hierarchical porous alumina loaded with 16.8% CuCl2 in an atmosphere of 80% relative humidity (including wet environment).
[0043] Fig.10 Schematic diagram of hierarchical porous alumina after metal halide loading.
[0044] Fig.11 Schematic diagram of the material after mixed adsorption of hierarchical porous alumina loaded with metal halides. DETAILED DESCRIPTION
[0045] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. Example 1
[0046] A method for preparing a modified adsorbent material for efficiently removing malodorous gases, the method comprising:
[0047] In terms of mass percentage, the components are: 16.8 parts of copper chloride, 100 parts of hierarchical porous alumina and 1250 parts of deionized water;
[0048] 16.8 parts of the modified substance copper chloride crystals were placed in a stainless steel beaker and 1250 parts of deionized water were added while stirring evenly;
[0049] Add the prepared metal salt solution to 100 parts of multi-level porous alumina and stir evenly to form a suspension state. Use an overhead mechanical stirrer to rotate at 300-500r / min for 1 hour at 50-60°C, then at 100-300r / min for 2 hours at 40-50°C, and finally at 20-100r / min for 3 hours at 30-40°C; Place the stainless steel beaker containing the mixture in a vacuum drying oven at 110°C and dry for 12 hours.
[0050] The dried material was calcined in nitrogen atmosphere by a heating device selected from a hot plate, a heating mantle, a muffle furnace, and a tube furnace. The calcination time was 2-16 hours. The calcination temperature was 400°C for 0.5 hours, then decreased to 300°C for 2 hours, and finally calcined at 200°C for 3 hours. A highly efficient modified adsorbent was obtained.
[0051] In this example, the performance of the high-performance modified adsorbent was tested. The carrier gas component is 0.4 MPa compressed air; the adsorption temperature is 20-60°C (preferably 35°C); the relative humidity of the adsorption bed is 40%-90% (preferably 70%); the mixed gas flow rate is 400-800 ml / min (preferably 500 ml / min); the ammonia to hydrogen sulfide concentration ratio is 1:1, and the total concentration of the mixed gas is 200-1200 ppm (preferably 600 ppm). Under this system, the ammonia penetration adsorption amount obtained in this example is 80-90 mg / g, and the hydrogen sulfide penetration adsorption amount is 180-220 mg / g.
[0052] from Figure 1-2 , all measured by BET under 77K nitrogen, the pore volume ratio range of the wide mesopores (pore size of 5-50nm) wide mesopores, narrow mesopores (pore size of 2-5nm) and micropores (pore size of 0-2nm) of the multi-level porous alumina used in the present invention is: narrow mesopore volume: micropore volume = 10%-30%: 20%-40%: 20%-40%; It can be seen that the multi-level porous alumina used in the present invention has a large number of micro-mesopores, and the pore structure of the multi-level porous alumina after loading the metal halide has no significant change, and the reduction in the cumulative pore volume further indicates that the metal halide is very reasonably present on the inner surface of the pore. The advantage of this carrier can ensure that the new substances generated during the adsorption reaction will not cause pore blockage, and the mixed gas can pass through the wide mesopores at the top to reach the narrow mesopores and micropores at the bottom, and fully react with the metal halide loaded inside the pore, thereby achieving a more ideal adsorption effect while reducing energy consumption. Example 2
[0053] The other operation steps in this embodiment are the same as those in Embodiment 1, except that, calculated by weight, 10 parts of the modified substance copper chloride, 100 parts of the multi-level porous alumina and 1250 parts of deionized water are weighed. Example 3
[0054] The other operation steps in this embodiment are the same as those in Embodiment 1, except that, calculated by weight, 15 parts of the modified substance copper chloride, 100 parts of the multi-level porous alumina and 1250 parts of deionized water are weighed. Example 4
[0055] The other operation steps in this embodiment are the same as those in Embodiment 1, except that, calculated by weight, 20 parts of the modified substance copper chloride, 100 parts of the multi-level porous alumina and 1250 parts of deionized water are weighed. Example 5
[0056] The other operation steps in this embodiment are the same as those in Embodiment 1, except that, calculated by weight, 25 parts of the modified substance copper chloride, 100 parts of the multi-level porous alumina and 1250 parts of deionized water are weighed.
[0057] According to the test conditions in Example 1, the modified materials obtained in Examples 1-5 were tested, and the experimental results are shown in Table 1. According to the experimental results in Table 1, it is preferred that the modified adsorbent with a loading of 15-20% can achieve a higher adsorption capacity, wherein the loading of 15-20% specifically refers to the use of 15-20 parts of copper chloride to modify 100 parts of multi-porous alumina by weight.
[0058] In terms of mass percentage, when the components are: 16.8 parts of copper chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water, the adsorption effect of the sample is optimal, the ammonia breakthrough adsorption amount is 87.12 mg / g, and the hydrogen sulfide breakthrough adsorption amount is 201.22 mg / g.
[0059] Table 1 Adsorption test results of Examples 1-5;
[0060]
[0061] Example 6
[0062] The other operation steps in this embodiment are the same as those in Embodiment 1, except that the modifying substance is nickel chloride. Calculated by weight, 20 parts of the modifying substance nickel chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water are weighed. Example 7
[0063] The other operation steps in this embodiment are the same as those in Embodiment 1, except that the modifying substance is magnesium chloride. Calculated by weight, 20 parts of the modifying substance magnesium chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water are weighed. Example 8
[0064] The other operation steps in this embodiment are the same as those in Embodiment 1, except that the modifying substance is zinc chloride. Calculated by weight, 20 parts of the modifying substance zinc chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water are weighed. Example 9
[0065] The other operation steps in this embodiment are the same as those in Embodiment 1, except that the modifying substance is calcium chloride. Calculated by mass, 20 parts of the modifying substance calcium chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water are weighed. Example 10
[0066] The other operating steps in this embodiment are the same as those in Embodiment 1, except that the modifying substance is copper chloride + magnesium chloride. Calculated by mass, 5-10 parts of the modifying substance copper chloride, 5-10 parts of the modifying substance magnesium chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water are weighed. Embodiment 11
[0067] The other operating steps in this embodiment are the same as those in Embodiment 1, except that the modifying substance is cupric chloride + nickel chloride + zinc chloride. Calculated by mass, 5-10 parts of the modifying substance cupric chloride, 5-10 parts of the modifying substance nickel chloride, 5-10 parts of the modifying substance zinc chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water are weighed. Example 12
[0068] The other operating steps in this embodiment are the same as those in Embodiment 1, except that the modifying substance is copper chloride + zinc chloride. Calculated by mass, 5-10 parts of the modifying substance copper chloride, 5-10 parts of the modifying substance zinc chloride, 100 parts of multi-level porous alumina and 1250 parts of deionized water are weighed.
[0069] According to the test conditions in Example 1, the modified materials obtained in Examples 6-12 were tested, and the experimental results are shown in Table 2. According to the experimental results in Table 2, the material modified with copper chloride is the most advantageous in mixed adsorption, and the modified adsorbent after coupling loading of two or more metal halides can also maintain good adsorption performance, and the adsorption amount is also correspondingly improved for different adsorbates.
[0070] Table 2 Adsorption test results of Examples 1, 6-, 12;
[0071]
[0072] Example 13
[0073] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, a constant temperature shaker is used to maintain stirring at 250-350 rpm at 50-60°C for 1 hour, then the speed is reduced to 150-250 rpm at 40-50°C for stirring for 2 hours, and finally the speed is maintained at 50-150 rpm at 30-40°C for stirring for 3 hours. Embodiment 14
[0074] The other operating steps in this embodiment are the same as those in Embodiment 1, except that this embodiment uses an overhead mechanical stirrer for non-step stirring at room temperature and maintains stirring at 600 r / min for 6 hours. Embodiment 15
[0075] The other operation steps in this embodiment are the same as those in Embodiment 1, except that this embodiment uses a constant temperature shaker at room temperature without graded stirring, and maintains stirring at 600 r / min for 6 hours. Example 16
[0076] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, the speed of an overhead mechanical stirrer is maintained at 300-500 r / min for stirring for 5 hours at room temperature, and then the speed is reduced to 100-300 r / min for stirring for 5 hours, and finally the speed is maintained at 20-100 r / min for stirring for 5 hours. Embodiment 17
[0077] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, the constant temperature shaker is maintained at 300-500 r / min for stirring for 5 hours at room temperature, and then the speed is reduced to 100-300 r / min for stirring for 5 hours, and finally the speed is maintained at 20-100 r / min for stirring for 5 hours.
[0078] According to the test conditions in Example 1, the modified materials obtained in Examples 13-17 were tested. The experimental results are shown in Table 3. It can be seen that different experimental results are obtained depending on the stirring time, stirring method, and whether or not the stirring is graded. There is no significant difference in the adsorption results obtained by the two stirring methods, while too long stirring time and non-graded stirring will have a greater impact on the adsorption effect.
[0079] Table 3 Examples 1, 13-17 adsorption test results;
[0080]
[0081] Embodiment 18
[0082] The other operation steps in this embodiment are the same as those in Embodiment 1, except that this embodiment is dried in a vacuum drying oven at 110° C. for 16 h. Embodiment 19
[0083] The other operation steps in this embodiment are the same as those in Embodiment 1, except that this embodiment is dried in a vacuum drying oven at 110° C. for 30 h. Embodiment 20
[0084] The other operation steps in this embodiment are the same as those in Embodiment 1, except that this embodiment is dried in a vacuum drying oven at 250° C. for 12 h.
[0085] According to the test conditions in Example 1, the modified materials obtained in Examples 18-20 were tested. The experimental results are shown in Table 4. It can be seen that different drying times and drying temperatures result in different experimental results. Too high a drying temperature will have a greater impact on the adsorption effect.
[0086] Table 4 Example 1, 18-20 adsorption test results;
[0087]
[0088] Embodiment 21
[0089] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, the dried sample is calcined in an inert gas atmosphere without stepping using a heating device selected from a hot plate, a heating mantle, a muffle furnace, and a tubular furnace, and the calcination temperature is maintained at 900° C. for 6 hours to obtain a high-efficiency modified adsorbent. Embodiment 22
[0090] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, the dried sample is calcined in an inert gas atmosphere without stepping using a heating device selected from a hot plate, a heating mantle, a muffle furnace, and a tubular furnace, and the calcination temperature is maintained at 400° C. for 6 hours to obtain a high-efficiency modified adsorbent. Embodiment 23
[0091] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, the dried sample is calcined in an inert gas atmosphere using a heating device selected from a hot plate, a heating hood, a muffle furnace, and a tubular furnace. The calcination is maintained at 400° C. for 6 h, then reduced to 300° C. for 6 h, and finally calcined at 200° C. for 6 h. Embodiment 24
[0092] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, the dried sample is calcined in an inert gas atmosphere using a heating device selected from a hot plate, a heating hood, a muffle furnace, and a tube furnace. The calcination is maintained at 400° C. for 0.5 h, then reduced to 300° C. for 1 h, and finally calcined at 200° C. for 1 h. Embodiment 25
[0093] The other operating steps in this embodiment are the same as those in Example 1, except that in this embodiment, the dried sample is calcined in an inert gas atmosphere using a heating device selected from a hot plate, a heating hood, a muffle furnace, and a tubular furnace. The calcination is maintained at 700° C. for 0.5 h, then reduced to 550° C. for 2 h, and finally calcined at 450° C. for 3 h.
[0094] According to the test conditions in Example 1, the modified materials obtained in Examples 21-24 were tested. The experimental results are shown in Table 5. It can be seen that different experimental results are obtained depending on the calcination time, calcination temperature, and whether the calcination is graded. Too high calcination temperature, too long calcination time, and non-graded calcination will have a greater impact on the adsorption effect.
[0095] Table 5: Adsorption test results of Examples 1, 21-25;
[0096]
[0097] Embodiment 26
[0098] The other operation steps in this embodiment are the same as those in Embodiment 1, except that the experimental sample used is fresh multi-level porous alumina without loading of metal halide. Embodiment 27
[0099] The other operating steps in this embodiment are the same as those in Embodiment 1, except that 100 parts of multi-level porous alumina in the modification process are replaced with 100 parts of traditional microporous alumina. Embodiment 28
[0100] The other operation steps in this embodiment are the same as those in Embodiment 1, except that the experimental sample used is fresh traditional microporous alumina without loading of metal halide.
[0101] According to the test conditions in Example 1, the materials obtained in Examples 26-28 were tested. The experimental results are shown in Table 6. It can be seen that the adsorption effect of alumina without metal halide loading is greatly reduced. This is mainly because the adsorption of ammonia and hydrogen sulfide is mainly chemical adsorption, which requires metal halide modification to provide more active sites and metal halide as a reactant to participate in chemical adsorption. Even if traditional microporous alumina is loaded with metal halide, its adsorption effect is very poor. This is because the metal halide loaded on its surface reacts with the adsorbate during the adsorption process, and the generated substance is blocked at the top of the pore and prevents the mixed gas from entering the pore and reacting with the metal halide loaded in the pore, resulting in poor adsorption effect.
[0102] In the present invention, the multi-level porous alumina (such as Fig.10 ) and schematic diagram of the mixed adsorption material (as shown Fig.11 As shown in the figure, the main pores of multi-level porous alumina are derived hierarchically, from the top of the pores to wide mesopores-narrow mesopores-micropores in sequence, which allows the wide mesopores at the top to have enough space to accommodate the H2S-NH3 adsorbed agglomerates produced by the adsorption reaction without causing blockage, so that the mixed gas can still enter the micropores at the bottom to react with the metal halide loaded in the pores, thereby making full use of the advantages of multi-level pores and greatly improving the adsorption efficiency.
[0103] Table 6 Example 1, 26-28 adsorption test results
[0104]
[0105] The modified adsorption material provided by the present invention can realize the adsorption of ammonia and hydrogen sulfide as single components respectively; and when water is present, the adsorption amount will be greatly increased, the presence of water vapor will promote the adsorption, and the coexistence of ammonia and hydrogen sulfide will have a better adsorption effect than single components. The specific reaction mechanism is as follows:
[0106] Take CuCl2 as an example to illustrate the single-component adsorption reaction mechanism (the reaction mechanisms of other metal chlorides are basically the same):
[0107] In the preparation process of modified adsorption materials, the active substance Cu(OH)Cl is generated by adding multi-level porous alumina to the metal halide solution and mixing. The principle is: the active centers on the surface of alumina are mainly unsaturated bonds and surface defects. At these locations, some oxygen atoms have lost one or more hydrogen atoms, forming oxygen vacancies, which have become one of the most common active centers. The negative charge on the oxygen vacancies is mainly distributed around them, forming a certain charge distribution, resulting in a strong polarity. The negative charge properties of the carrier surface will attract H in water molecules during the mixing process. + , forming Brønsted acid sites on the support surface, and the remaining OH - will react with Cu in the solution 2+ , Cl - Cu(OH)Cl and Cu(OH)2 are formed. Cu(OH)2 and Cu(OH)Cl mainly exist in the large number of pores of multi-level porous alumina, and also partially exist on the outer surface of the pores. In the calcination step, the copper chloride on the surface of the carrier will be decomposed by high temperature to form cuprous chloride. The valence of copper in cuprous chloride is +1. Therefore, after impregnation with copper chloride aqueous solution, the main form of active substances on the inner / outer surface of the carrier is Cu 2+ There are also some Cu + .Cu 2+ The main copper is in the form of CuCl2 hydrate (CuCl2·2H2O) or basic copper chloride Cu(OH)Cl (forming some Brønsted acid sites).+ It exists in the form of CuCl crystals.
[0108] In addition, the concentration of the metal halide solution used in the present invention is 0.2-0.5 mol / L and is green in color. According to common sense, the yellow color of CuCl2 aqueous solution is due to the formation of [CuCl4] 2- The coordination ion is blue because it forms [Cu(H2O)4] 2+ Coordination ions, when the two coexist, they appear green; therefore, the metal halide solution used in the present invention also includes [Cu(H2O)4] 2+ and [CuCl4] 2- Coordination ions; two coordination ions are loaded on the carrier and can directly generate copper ammonia complex in the single component NH3.
[0109] These two coordinated ions will directly complex with NH3 and increase its adsorption capacity.
[0110] After the modified adsorption material provided by the present invention adsorbs NH3 under dry gas and wet gas conditions, the valence state of copper does not change significantly, indicating that no redox reaction occurs when adsorbing NH3.
[0111] Under dry gas conditions, Cu 2+ 、NH3、Cl - Under natural conditions, complexation will occur to generate deep blue copper-ammonia coordination ion Cu[(NH3)x]Cl2; it is preliminarily judged that the complex is similar to the crystal form of Cu(OH)Cl loaded on the surface of the carrier, forming clusters, thereby achieving adsorption; and the CuCl2·2H2O on the surface of the carrier reacts with NH3 and HCl (the ionic form of the surface) to generate (NH4)2CuCl4·2H2O, thereby achieving adsorption.
[0112] Under humid conditions, the adsorbent NH3 dissolves in water to generate NH4 + The addition of water promotes Cl - Ionization, a large amount of Cl - Ionization will also react with NH4 + The ammonium salt NH4Cl is generated, thereby promoting the formation of (NH4)2CuCl4·2H2O. Combined with the N1s spectrum in XPS Figure 6-7 From the above, after adding water, more N in the form of ammonium radicals appeared on the surface of the material, that is, the four chemical bonds around N were NH4 + The addition of water further confirms that the addition of water promotes the adsorption of NH3. At the same time, the crystal form of (NH4)2CuCl4·2H2O is similar to that of Cu(OH)Cl, indicating that the addition of water makes NH3 and water affinity, forming more NH4 + ions, thereby promoting the formation of (NH4)2CuCl4·2H2O, and then achieving adsorption.
[0113] After the modified adsorption material provided by the present invention adsorbs H2S under dry gas or wet gas conditions, the valence state of S undergoes various changes, indicating that a redox reaction occurs in the adsorbed H2S.
[0114] Under dry gas conditions, CuCl2 and CuCl loaded on the inner / outer surface of the carrier will react with H2S to generate CuS and Cu2S. In the presence of oxygen, Cu can act as an oxygen activation catalyst to oxidize H2S and convert it into elemental sulfur H2S+O2→S+H2O, H2S+SO2→S+H2O. At the same time, part of the generated Cu2S will also react with the remaining CuCl2 loaded on the surface of the carrier to generate elemental S and CuCl.
[0115] Under humid conditions, water vapor condenses into a water film in the pores of the material, promoting the dissolution and dissociation of H2S to produce H + and HS − Ions enter the water film. Oxygen is activated by the splitting of the OO bond. After H2S dissociates, oxygen oxidizes the sulfide ions present in the water film to generate S element. The addition of water causes the S element to react with oxygen and oxidize into SO3 2- or SO4 2- , the generated SO4 2- Then with Cu 2+ The reaction generates CuSO4. Combined with the S2p spectrum in XPS Figure 8-9 It can be seen that after adding water, more SO3 appeared on the surface of the material 2- or SO4 2- In the desulfurization process, catalytic oxidation, sulfate generation and reactive adsorption generate elemental sulfur, CuSO4 and CuS respectively. The complete removal of H2S is mainly based on reactive adsorption. The generated elemental sulfur or sulfate and sulfide are tightly bound to the activation site and are not easy to regenerate.
[0116] Take CuCl2 as an example to illustrate the mixed adsorption reaction mechanism (the reaction mechanisms of other metal chlorides are basically the same):
[0117] The H2S dissociation process can be simply regarded as two hydrogen atoms separating from H2S one by one. As H2S moves toward the surface plane of the material, the bond length of SH begins to lengthen, and the hydrogen atom reaches the surface of the material. In this step, a Brønsted acid site is formed. The formed B acid site can further increase the adsorption of NH3;
[0118] The addition of water can significantly increase the adsorption energy of H2S because the addition of water promotes the 2+ , Cl - NH 4+ It becomes ionized and produces NH4Cl, (NH4)2CuCl4, etc.
[0119] The addition of water will promote the dissociation of H2S and form a water film on the surface of the material. The water film will absorb oxygen, and NH3 and H2O will promote the oxidation of S to generate more SO4. 2- , accelerating the oxidation process of H2S.
[0120] In Cu 2+ , Cl - NH 4+ In the process of forming (NH4)2CuCl4, 4 Cl - But only occupies 1 Cu 2+ , the extra 1 Cu 2+ It can be used to react with H2S to generate CuS, thereby achieving mutual promotion of adsorption of NH3 and H2S.
[0121] Ionic Cu 2+ NH 4+ 、SO3 2- 、SO4 2- Will react to form (NH4)2Cu(SO4)2·6H2O, (NH4)2SO3, NH4HSO3. For examples with positive and negative charges, they attract each other to form new substances. Figure 3-5 , XRD characterization results of the materials.
[0122] Figure 3 ① is the XRD characterization diagram of the carrier multi-level porous alumina; ② is the XRD characterization diagram of the fresh sample of the carrier multi-level porous alumina loaded with 16.8% CuCl2; ③ is the XRD characterization diagram of the sample loaded with 16.8% CuCl2 after single component adsorption of H2S and penetration in a dry atmosphere; ④ is the XRD characterization diagram of the sample loaded with 16.8% CuCl2 after single component adsorption of H2S and penetration in an atmosphere with 80% relative humidity. By comparing the peaks of ① and ②, it can be seen that the inner / outer surface of the carrier is fully loaded with the modified substance, and the main form of the inner / outer surface of the carrier after impregnation with CuCl2·2H2O is Cu 2+ There are also some Cu + .Cu 2+ Mainly copper, in the form of CuCl2 hydrate or basic copper chloride Cu(OH)Cl (forming some Brønsted acid sites), Cu + It exists in the form of CuCl crystals. By comparing the peaks of ② and ③, it can be seen that the adsorption of H2S in a dry atmosphere is mainly chemical adsorption, mainly generating sulfides CuS and Cu2S, and a small part is oxidized to generate elemental S. By comparing the peaks of ③ and ④, it can be seen that in an atmosphere with a relative humidity of 80% (including a humid environment), the main reaction is that water vapor condenses into a water film in the pores of the material to promote the dissolution and dissociation of H2S to produce H + and HS −Ions enter the water film. Oxygen is activated by the splitting of the OO bond. After H2S dissociates, oxygen oxidizes the sulfide ions present in the water film to generate S element. The addition of water causes the S element to react with oxygen and oxidize into SO3 2- or SO4 2- , the generated SO4 2- Then with Cu 2+ The reaction produces CuSO4.
[0123] Figure 4 ① is the XRD characterization diagram of the carrier multi-level porous alumina; ② is the XRD characterization diagram of the fresh sample of the carrier multi-level porous alumina loaded with 16.8% CuCl2; ③ is the XRD characterization diagram of the sample loaded with 16.8% CuCl2 after single component adsorption of NH3 and penetration in a dry atmosphere; ④ is the XRD characterization diagram of the sample loaded with 16.8% CuCl2 after single component adsorption of NH3 and penetration in an atmosphere with 80% relative humidity. By comparing the peaks of ②③, it can be seen that in a dry atmosphere, Cu 2+ 、NH3、Cl - Under natural conditions, complexation will occur to generate deep blue copper-ammonia coordination ions Cu [(NH3)x]Cl2. The CuCl2·2H2O on the surface of the carrier will react with NH3 and HCl (the ionic form on the surface) to generate (NH4)2CuCl4·2H2O. By comparing the peaks of ③ and ④, it can be seen that in an atmosphere with a relative humidity of 80% (including a humid environment), the addition of water promotes the Cl - Ionization, a large amount of Cl - Ionization will also react with NH4 + Ammonium salt NH4Cl is generated, thereby promoting the formation of (NH4)2CuCl4·2H2O.
[0124] Figure 5 Figure ① is the XRD characterization diagram of the sample of multi-level porous alumina loaded with 16.8% CuCl2 after H2S and NH3 mixed adsorption in an atmosphere of 80% relative humidity; Figure ② is the XRD characterization diagram of the sample of multi-level porous alumina loaded with 16.8% CuCl2 after H2S and NH3 mixed adsorption in a dry atmosphere. By comparing the peaks of ① and ②, it can be seen that the addition of water in the mixed adsorption of H2S and NH3 will promote the dissociation of H2S and form a layer of water film on the surface of the material. The water film will absorb oxygen, and NH3 and H2O will promote the oxidation of S and generate more SO4 2- , accelerating the oxidation process of H2S. 2+ , Cl - NH 4+ In the process of forming (NH4)2CuCl4, 4 Cl - But only occupies 1 Cu 2+ , the extra 1 Cu 2+It can be used to react with H2S to generate CuS, thereby achieving mutual promotion between NH3 and H2S. 2+ NH 4+ 、SO3 2- 、SO4 2- It will react to produce (NH4)2Cu(SO4)2·6H2O, (NH4)2SO3, and NH4HSO3.
[0125] Figure 6-7 This is the XPS N1s spectrum of the sample with 16.8% CuCl2 loaded on hierarchical alumina after H2S and NH3 mixed adsorption in dry atmosphere / 80% relative humidity (including wet environment). It can be seen that after adding water, more N in the form of ammonium radicals appeared on the surface of the material, that is, the four chemical bonds around N are NH4 + The addition of water further confirms that the addition of water promotes the adsorption of NH3. At the same time, the crystal forms of Cu(NH3)xCl2 and Cu(OH)Cl are similar, indicating that the addition of water makes NH3 and water affinity, forming more NH 4+ ions, thus promoting the next reaction.
[0126] Figure 8-9 This is the XPS S2p spectrum of the sample with 16.8% CuCl2 loaded on the multi-level porous alumina after H2S and NH3 mixed adsorption in a dry atmosphere / 80% relative humidity (including wet environment). It can be seen that after adding water, more SO3 appeared on the surface of the material 2- or SO4 2- During the desulfurization process, catalytic oxidation, sulfate generation and reactive adsorption generate elemental sulfur, CuSO4 and CuS respectively. The complete removal of H2S is mainly based on reactive adsorption. 2+ NH 4+ 、SO3 2- 、SO4 2- It will react to produce (NH4)2Cu(SO4)2·6H2O, (NH4)2SO3, and NH4HSO3, thereby achieving mutual promotion between NH3 and H2S.
[0127] The above is the adsorption mechanism of ammonia and hydrogen sulfide by the modified adsorption material in a humid environment. It can be seen that the mixed adsorption in a humid environment is not a single adsorption. The copper chloride modification can not only form a complex with NH3, but also react chemically with H2S. The material is water-resistant and achieves a high adsorption amount under the coexistence of sulfur, ammonia and water in a humid environment, which is even higher than the adsorption amount of each single component and dry gas, further reflecting the high efficiency of the chemical adsorption site. The modified material of the present invention synergistically achieves ammonia complex enhanced adsorption and H2S catalytic oxidation.
[0128] It can be seen that the adsorption behavior of the modified adsorption material provided by the present invention is mainly chemical adsorption, the carrier can provide more pores to make the modified substance more fully loaded on its inner / outer surface, and the introduction of metal halides can cause the microstructure of the porous alumina surface to change and form defect sites. These surface defects can serve as active sites, which have a stronger affinity for gases such as ammonia and hydrogen sulfide, thereby increasing the adsorption rate and capacity; providing the activation energy required for adsorption of active substances and catalytic reactions. The charge distribution and chemical properties of the porous alumina surface can also be adjusted to make it more active. Therefore, metal halide modification forms more active sites on the porous alumina surface, which have a stronger affinity for gases such as ammonia and hydrogen sulfide, thereby increasing the adsorption rate and capacity.
[0129] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For ordinary technicians in this field, they can still modify or transform the technical solutions described above, which all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a modified adsorbent material for efficiently removing malodorous gases, characterized in that: The multi-level porous alumina is modified by metal halide to obtain a modified adsorption material for efficiently removing malodorous gases, wherein the malodorous gases include ammonia and / or hydrogen sulfide; The pore structure of the multi-level porous alumina includes wide mesopores, narrow mesopores and micropores; the pore size of the wide mesopores is 5-50nm, the pore size of the narrow mesopores is 2-5nm, and the pore size of the micropores is 0-2nm; the pore volume ratio of the wide mesopores, narrow mesopores and micropores is in the range of: wide mesopore volume: narrow mesopore volume: micropore volume = 10%-30%: 20%-40%: 20%-40%; the specific surface area of the multi-level porous alumina is ≥250m 2 / g, and the average pore size of the multi-level porous alumina is ≥5nm; The method comprises the following steps: (1) Dissolving metal halide in water to form a metal halide solution, adding multi-level porous alumina, and using a constant temperature shaker or an overhead mechanical stirrer to perform gradient graded stirring; (2) placing the mixture treated in step (1) in a vacuum drying oven for drying; (3) calcining the material obtained by drying in step (2) in a stepwise manner to prepare a modified adsorption material for efficiently removing ammonia and / or hydrogen sulfide; In step (3), the conditions of the step-by-step calcination are: first calcining at 350-450°C for 0.5-4h, then calcining at 250-350°C for 0.5-4h, and finally calcining at 150-250°C for 1-4h.
2. The method for preparing a modified adsorbent material for efficiently removing malodorous gases according to claim 1, characterized in that: The metal halide includes any one or more of copper chloride, nickel chloride, magnesium chloride, calcium chloride and zinc chloride.
3. The method for preparing a modified adsorbent material for efficiently removing malodorous gas according to claim 2, characterized in that: The metal halide is cupric chloride or a combination of cupric chloride and one or more of nickel chloride, magnesium chloride, calcium chloride and zinc chloride.
4. The method for preparing a modified adsorbent material for efficiently removing malodorous gas according to claim 1, characterized in that: In step (1), the shaking rate and temperature change of the constant temperature shaker meet the following conditions: shaking at 250-350 rpm at 50-60°C for 1-3 hours, then shaking at 150-250 rpm at 40-50°C for 1-3 hours, and finally shaking at 50-150 rpm at 30-40°C for 1-3 hours; The rotation speed and temperature change of the overhead mechanical stirrer meet the following conditions: rotate at 300-500 r / min for 1-3 hours at 50-60°C, then rotate at 100-300 r / min for 1-3 hours at 40-50°C, and finally rotate at 20-100 r / min for 1-3 hours at 30-40°C; In step (1), the metal halide accounts for 2-50 parts by mass, and the multi-level porous alumina accounts for 100 parts; the concentration of the metal halide in the metal halide solution is 0.2-0.5 mol / L.
5. The method for preparing a modified adsorbent material for efficiently removing malodorous gas according to claim 1, characterized in that: In step (2), the drying method is vacuum drying, and the drying conditions are: drying temperature 100-180° C., and drying time 0.5-16 h.
6. A modified adsorbent material for efficiently removing malodorous gases, prepared by the method according to any one of claims 1 to 5, characterized in that: The modified adsorption material includes a multi-level porous alumina carrier and an active substance loaded on the carrier; the active substance loaded on the carrier includes M x Cl y ·nH2O、M x (OH) y Cl z ; Among them, x ranges from 1 to 6, y ranges from 1 to 8, z ranges from 1 to 6, n ranges from 1 to 10, and M corresponds to copper, nickel, magnesium, calcium, and zinc metals.
7. A modified adsorbent material for efficiently removing malodorous gases according to claim 6, characterized in that: The concentration of ammonia or hydrogen sulfide in the mixed gas is 100ppb-6000ppm. In a humid environment with a relative humidity of 5%-100%, the penetration adsorption amount of ammonia and hydrogen sulfide of the modified adsorption material reaches 40mg / g and 100mg / g respectively.
8. An application of the modified adsorption material according to claim 6, characterized in that: The modified adsorbent material is used for the adsorption and removal of ammonia or hydrogen sulfide; and the modified adsorbent material is used for the combined synchronous adsorption and removal of ammonia and hydrogen sulfide in a mixed gas of ammonia and hydrogen sulfide in a humid environment; after the modified adsorbent material adsorbs ammonia and / or hydrogen sulfide, when the desorption temperature reaches 250-300°C, the desorption rate of the modified adsorbent material reaches 70-90%.
Citation Information
Patent Citations
Composite metal modified hierarchical pore molecular sieve catalyst and preparation method and application thereof
CN112295590A
Desulfurization method and system
CN112642255A
Alkaline earth metal halide ammonia gas composite adsorbent and preparation method thereof
CN115814756A
Improvements in the process of removing ammonia from gases
GB495026A
